Genome-wide discovery and verification of novel structured RNAs in Plasmodium falciparum - Mourier, Tobias; Carret, Celine; Kyes, Sue; Christodoulou, Zoe; Gardner, Paul P.; Jeffares, Daniel C.; Pinches, Robert; Barrell, Bart; Berriman, Matt; Griffiths-Jones, Sam; Ivens, Alasdair; Newbold, Chris; et al.

(untitled) (Genome Research, 2008)
We undertook a genome-wide search for novel noncoding RNAs (ncRNA) in the malaria parasite Plasmodium falciparum. We used the RNAz program to predict structures in the noncoding regions of the P. falciparum 3D7 genome that were conserved with at least one of seven other Plasmodium spp. genome sequences. By using Northern blot analysis for 76 high-scoring predictions and microarray analysis for the majority of candidates, we have verified the expression of 33 novel ncRNA transcripts including four members of a ncRNA family in the asexual blood stage. These transcripts represent novel structured ncRNAs in P. falciparum and are not represented in any RNA databases. We provide supporting evidence for purifying selection acting on the experimentally verified ncRNAs by comparing the nucleotide substitutions in the predicted ncRNA candidate structures in P. falciparum with the closely related chimp malaria parasite P. reichenowi. The high confirmation rate within a single parasite life cycle stage suggests that many more of the predictions may be expressed in other stages of the organism’s life cycle.